Surface wave interaction with a vertical viscoelastic barrier - Bi, Cheng (2022)
In this study, the surface wave interaction with a thin vertical submerged viscoelastic sheet as a wave barrier is investigated analytically without pre-assumption of the sheet dynamic behavior. The viscoelastic sheet spans over the entire water depth, and is tensioned and hinged on both ends. The Voigt model is employed for the viscoelastic representation. Analytical solutions are obtained using the eigenfunction expansion method with the hydroelastic and viscoelastic parameters of α and β, respectively. Five hydro-viscoelastic regimes with varying tension from elastic plate to inelastic membrane are identified based on the analysis. As the regime changes from plate-like to membrane-like, the wave transmission diminishes and the sheet boundary displacement together with the flexural strain and shear force reduce, while the corresponding resonating wavenumber increases instead. The sheet response with tension-resistance dominance is more dependent on α than that with bending-resistance dominance. Furthermore, as the sheet transits from tension- to bending-resistance dominance, the reduction of wave transmission with β near the resonating wavenumber becomes significant due to the internal energy dissipation.